Differences In The Length Of Labor Stage II On Upright Position and Recumbent Position - Rizki, Lailatul Khusnul; Windarti, Yunik (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The delivery process is determined by several factors that influence it, one of which is from the mother and fetus side (Psychology, Power, Passage, Passanger, Position and Placenta). Childbirth can proceed normally (Euthocia) if these factors are met properly. This type of research is an observational study using a comparative study and a cross sectional approach, namely observing the position of labor (upright position and recumbent position) and observing the duration of second labor. The population in this study were mothers who gave birth at PMB Sari Nurhayati. The sampling technique used purposive sampling. The results of the Mann Whitney test analysis showed ρ value of 0.009 (ρ <0.05), which means that there is a significant difference between the upright position and the recumbent position. The average length of time II in the upright position was 11.3 minutes, while in the recumbent position group was 19.7 minutes.